The impact of economic performance on voting behavior in Turkey - Benli, Kınay Barkın. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Dynamics of voting behavior and political party preferences have long been an issue of debate. Throughout time, different views and theories about the voting behavior have been analyzed in various research. Today, voters increasingly become aware of their economic and political environment. Thus, factors that affecting the voting behavior has become an important factor for the both political parties and voters. With this background, this study examines economic performance and non-economic performance of incumbent parties and their relationship with the voters’ voting behavior in Turkey. The sample includes 659 participants who are active voters in Istanbul, Turkey. Data were gathered from face to face surveys. The impact of control variables such as age, gender, household income, education level and the independent variables such as current economic perception of voters, future economic expectations under the incumbent party rule, non-economic performance the incumbent party and voting factors have been examined in the context of responsibility theory of voting behavior. Findings of the study proves that, in Turkey, voters consider economic factors such as current economic perception and future expectations on their political party preferences and reward or punish the incumbent according to their economic performance.
Keywords: Voting research -- Turkey.; Economic policy -- Turkey.